Distribution of the entodiniomorphid ciliate Troglocorys cava Tokiwa, Modrý, Ito, Pomajbíková, Petrželková, & Imai, , (Entodiniomorphida: Blepharocorythidae) in wild and captive chimpanzees. - Sá, Rui (2013)
Trophozoites of Troglocorys cava were detected in all but one of the wild chimpanzee populations from Rubondo Island (Tanzania), with a prevalence ranging between 20% and 78%. However, the ciliate was absent in all captive groups. Prevalence appeared to increase with the number of sequential samples taken from a particular individual and reached 95.5% in wild individuals sampled at least 4 times.